Precision livestock farming applied to the dairy sector: 50 years of history with a text mining and topic analysis approach - Lucia Trapanese; Giovanna Bifulco; Alfio Calanni Macchio; Francesca Aragona; Sissy Purrone; Giuseppe Campanile; Angela Salzano (Smart Agricultural Technology)
The global dairy industry has been revolutionized by advancements in genetics, milking technology, nutrition, and farm management, leading to increased milk production per cow and a substantial rise in total annual milk output. These changes have pushed the dairy industry toward a more technological approach that, with the aid of precision livestock farming (PLF), has maximized the production per cow. This study explores the evolution of PLF literature over time. It identifies its key topics, aiming to clarify and categorize the various areas of interest related to this field, trying to underscore potentiality and existing knowledge gaps. A comprehensive search on the Scopus® bibliometric database was carried out using various related keywords such as: “precision livestock farming, sensors, machine learning and dairy”. The research identified 5362 papers published from January 1976 to April 2024 that, after filtering, became 1794 eligible records. Descriptive statistics revealed a significant exponential increase in studies on PLF in dairy since 2000, particularly in developed countries with a long story of dairy breeding. Text mining and topic analysis revealed that the most frequently mentioned terms were “milk”, “behaviour” and “model”, suggesting 'suggesting that animal welfare and work based on data drive process have to be considered to improve production. Based on the findings of this literature review, it is evident that PLF had an impact on animal welfare, lifestyle of farmers and production efficiency. Addressing one area often influences others: thus, all these aspects are interrelated, with PLF being a key link between them.